Use of routinely collected data on trihalomethane in drinking water for epidemiological purposes. Issue 7 (1st July 2001) - Keegan, T; Whitaker, H; Nieuwenhuijsen, M J; Toledano, M B; Elliott, P; Fawell, J; Wilkinson, M; Best, N
Abstract : OBJECTIVES: To explore the use of routinely collected trihalomethane (THM) measurements for epidemiological studies. Recently there has been interest in the relation between byproducts of disinfection of public drinking water and certain adverse reproductive outcomes, including stillbirth, congenital malformations, and low birth weight. METHOD: Five years of THM readings (1992–6), collected for compliance with statutory limits, were analysed. One water company in the north west of England, divided into 288 water zones, provided 15 984 observations for statistical analysis. On average each zone was sampled 11.1 times a year. Five year, annual, monthly, and seasonal variation in THMs were examined as well as the variability within and between zones. RESULTS: Between 1992 and 1996 the total THM (TTHM) annual zone means were less than half the statutory concentration, at approximately 46 μg/l. Differences in annual water zone means were within 7%. Over the study period, the maximum water zone mean fell from 142.2 to 88.1 μg/l. Mean annual concentrations for individual THMs (μg/l) were 36.6, 8.0, and 2.8 for chloroform, bromodichloromethane (BDCM), and dibromochloromethane (DBCM) respectively. Bromoform data were not analysed, because a high proportion of the data were below the detection limit. The correlation between chloroform and TTHM was 0.98, between BDCM and TTHM 0.62, and between DBCM and TTHM −0.09. Between zone variation was larger than within zone variation for chloroform and BDCM, but not for DBCM. There was only little seasonal variation (<3%). Monthly variation was found although there were no consistent trends within years. CONCLUSION: In an area where the TTHM concentrations were less than half the statutory limit (48 μg/l) chloroform formed a high proportion of TTHM. The results of the correlation analysis suggest that TTHM concentrations provided a good indication of chloroform concentrations, a reasonable indication of BDCM concentrations, but no indication of DBCM. Zone means were similar over the years, but the maximum concentrations reduced considerably, which suggests that successful improvements in treatment have been made to reduce high TTHM concentrations in the area. For chloroform and BDCM, the main THMs, the component between water zones was greater than variation within water zones and explained most of the overall exposure variation. Variation between months and seasons was low and showed no clear trends within years. The results indicate that routinely collected data can be used to obtain exposure estimates for epidemiological studies at a small area level.